Religion, Sustainable Development and Policy: Principles to Practice. (May 2016) - Narayanan, Yamini
Abstract: The nexus between religion and development is now well recognized in scholarship but the implications for development policies are relatively unexplored. The challenge with analysing religion as a policy construct is to ensure that its rich anthropological dimensions are not lost, but rather that these inform the conception and implementation of development planning, especially in diverse, multireligious societies. The aim of this special issue is to unpack the complex anthropological, sociological and even theological dimensions of religion that can enable development policymakers to identify the ways in which religion shapes the society, the environment and the economy. Therein also lie the opportunities to articulate policies that are truly responsive to serious structural issues of inequalities and oppressions. The authors address five foci that are central to sustainable development policymaking – urbanization and spatial equality; gender justice; environment and human/animal tensions; economic growth; and postsecularity and governance. Copyright © 2016 John Wiley & Sons, Ltd and ERP Environment.